Analisis Efisiensi Turbin Gas Tipe V94.2 Sebelum Dan Sesudah Minor Inspection Pada Blok 4 Unit 3 Pltgu Muara Tawar - Hendri ST MT; Rakha Syammary (Sekolah Tinggi Teknik - PLN, 2020)
With the development of technological advances that are very rapid and affect the energy needs, especially electrical energy, as well as increasing demand for power plants such as PLTA, PLTU, PLTGU, PLTD, PLTD, PLTP and others must work extra for the convenience and needs of consumers. Therefore, lately it often happens that generators are experiencing problems and make the efficiency of these generators decrease, which can make consumers uncomfortable and the needs of consumers are not met to the maximum. In particular PLTG which consists of several main components, namely compressors, gas turbines, combustion chambers, and generators which in operation use equipment that has been integrated with one another. Therefore here the author tries to calculate and analyze the efficiency of the gas turbine used in the Muara Tawar PLTGU before and after the holding of the Minor Inspection with the Bryton cycle method and from that method will obtain thermal efficiency in the gas turbine. So that the Minor Inspection can actually improve the performance of the Gas Turbine by increasing the actual thermal efficiency. The results of calculations after Minor Inspection thermal efficiency has increased by 0.70%, compressor efficiency has increased 0.56%, combustion chamber efficiency has increased 0.27%, turbine efficiency has increased 1.35%.